The Effect of Self Assessment Towards Students' Writing Competency - Tari, Nirmala; Dianita Safitri, Ni Putu (Jurnal Manajemen Pelayanan Hotel, 2023)
This research is discussed finding the effect of self-assessment on students’ writing competency in the English Elementary Level Course. There was an observation before conducting this research to find out students’ writing competency. This research was done in Akademi Komunitas Manajemen Perhotelan Indonesia especially on Elementary Level Course Students. It was located in Kuta Utara District, Badung Regency. In the academic year 2022/2023, this level has 5 classes. This research was done for 6 months which were divided into 3 phases, namely: preparation and proposal, data collection, and finishing. Preparation and proposal were done in 3 months starting from June 2022 until August 2022. Data collection was done in 1.5 months starting from the end of August until the beginning of October 2022. Lastly, finishing was done for 1.5 months after the data were acquired. Based on the finding and discussion, the conclusion can be made as There is no significant effect of self-assessment on students’ writing competency separately. It is proven from the Sig value of 0.984 which is higher than 0.05. The English teachers are suggested to apply self-assessment in irregular classes, not online learning. It is because some problems might make self-assessment ineffective. The students are suggested to be open if they have problems understanding and implementing self-assessment. furthermore, they also have to be serious during online classes to achieve learning goals. Keywords: Writing Competency, and Self-Assessment